The Knowledge Status of Coastal and Marine Ecosystem Services - Challenges, Limitations and Lessons Learned From the Application of the Ecosystem Services Approach in Management - Carrasco De La Cruz, Pedro Manuel (Frontiers in Marine Science, 2021)
The concept of ecosystem services (ES), first introduced in 1970’s, gained mainstream attention in 2005, when the Millennium Ecosystem Assessment formally proposed a definition for it. In spite of the attention, many aspects about the ES concept have remained controversial, i.e., their classification, value, generation, link to human well-being, and supportive role as management tool. This review explores the knowledge status of ecosystem services, focusing on those services generated in coastal and marine environments (CMES). A knowledge gap and an underdevelopment of tools to assess CMES is evident in the literature, especially when compared to the progress done in the assessment of land ES. Possible explanations reside on the yet small proportion that the research done on CMES represents for the ecosystem service framework (ESF), in part due to the intrinsic challenges of researching the marine environment, but also due to the limited availability of spatial data on marine ecosystems. Nevertheless, the ES concept is getting more attention towards policy-makers and stakeholders, leading to the implementation of an ecosystem services approach (ESA) to the management and protection of CMES. Six lessons are rescued from the literature to improve the ESA: 1) integration of the ESA in a science-policy process; 2) more simplicity for the CMES prediction models; 3) move towards empowering of stakeholders; 4) integration of the value pluralism of CMES with less focus on money; 5) the link of ES to Human Well-being must not been forgotten; and 6) communication of results and social literacy are key.